Do Firms Hire More Older Workers? Evidence from Germany - Fabian Busch; Robert Fenge; Carsten Ochsen (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses how demographic changes of the labour force affect labour demand. Do firms adjust their hiring behaviour to an ageing society? Combining data at the firm level and the administrative district level, we analyse the hiring behaviour of firms. Our findings suggest that firms with an ageing workforce hire relatively more older workers. Since the willingness to hire older workers also increases with the share of older unemployed, the propensity to employ older people does generally rise with an ageing labour force. Also, part-time employment induces firms to engage more older workers but this effect disappears for large firms. In contrast, partial retirement regulations have a negative effect on hiring older workers which reveals unintended incentives of the German law on this matter. Finally, firms with a higher share of educated personnel demand more older workers.
Keywords: J11; J23; C33; 330; ageing labour force; hiring of older workers; panel data models